2022
DOI: 10.1038/s41409-021-01555-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of a new clinically-based classification system in patients with CMML undergoing allogeneic HCT: a retrospective analysis of the EBMT-CMWP

Abstract: Recently a new three-group clinical classification was reported by an International Consortium to stratify CMML patients with regard to prognosis. The groups were defined as follows: (1) Myelodysplastic (MD)-CMML: WBC ≤ 10 × 10 9 /l, circulating immature myeloid cells (IMC) = 0, no splenomegaly; (2) MD/MP (overlap)-CMML: WBC 10-20 × 10 9 /l or WBC ≤ 10 × 10 9 /l but IMC > 0 and/or splenomegaly; (3) Myeloproliferative (MP)-CMML: WBC > 20 × 10 9 /l. By analysing EBMT Registry patients who underwent allo-HCT for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…48,49 According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years. 4,35,50 We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan With the development and advancement of nonmyeloablative and reduced-intensity allogeneic stem cell transplantation, significant progress has been made over the past decade in allo-HSCT for elderly patients. [64][65][66] However, defining the best treatment strategy for allo-HSCT for elderly patients remains a difficult decision since the combination of chronic underlying disease, the accumulation of long-term chemotherapy drugs, the potential toxicity of conditioning regimens (including cases of microangiopathy and cardiotoxicity), the risks of GVHD, impaired immune reconstitution, and the need for prolonged immunosuppression may be of major concern in these vulnerable patients with complex needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years. 4,35,50 We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan With the development and advancement of nonmyeloablative and reduced-intensity allogeneic stem cell transplantation, significant progress has been made over the past decade in allo-HSCT for elderly patients. [64][65][66] However, defining the best treatment strategy for allo-HSCT for elderly patients remains a difficult decision since the combination of chronic underlying disease, the accumulation of long-term chemotherapy drugs, the potential toxicity of conditioning regimens (including cases of microangiopathy and cardiotoxicity), the risks of GVHD, impaired immune reconstitution, and the need for prolonged immunosuppression may be of major concern in these vulnerable patients with complex needs.…”
Section: Discussionmentioning
confidence: 99%
“…According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years 4,35,50 . We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan 16,22,27 and China, 6,43,49,56–63 ), and the results showed that the median age of CMML patients in Eastern countries was younger (38–70 years vs. 44–73 years), and the median age of CMML patients undergoing allo‐HSCT was similar in Eastern and Western countries (38–63 years vs. 44–64 years). However, the age of CMML patients undergoing allo‐HSCT was lower in both Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Likewise, the role of allo-HCT in CMML, especially in elderly patients, remains unclear. Over the years, a number of clinical research efforts have attempted to establish optimal prognostic scores for CMML patients undergoing allo-HCT 39,40 ; however, the limited number of patients analyzed in the different and heterogeneous series has represented a major limitation. 41 Therefore, in this retrospective EBMT registry-based study, we aimed to identify factors associated with allo-HCT outcomes in CMML patients, particularly focusing on age, and to compare them with a population of MDS patients undergoing allo-HCT in the same period.…”
Section: Introductionmentioning
confidence: 99%